PENGARUH KOMPETENSI KERJA, LOYALITAS KERJA, DISIPLIN KERJA DAN TUNJANGAN KINERJA TERHADAP KINERJA KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA BANTUL - Hadiyanto, Muhammad Fuad; Syaflan, Meidi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to analyze the influence of work competence, work loyalty, work discipline, and performance allowances on the performance of the Bantul Pratama Tax Office employees. This type of research uses a descriptive analysis method with a quantitative approach. Data collection was carried out using the questionnaire method and data analysis was tested using SPSS software. The population and sample in this study were all employees registered at KPP Pratama Bantul, totaling 87 respondents. The results of this study prove that partially work competence has a positive and significant influence on employee performance at the Bantul Pratama Tax Service Office. Partial work loyalty has a positive and significant effect on employee performance at the Bantul Primary Tax Service Office. Work discipline partially has a positive and significant influence on employee performance at the Bantul Primary Tax Service Office. Performance Allowance partially has a positive and significant influence on employee performance at the Bantul Primary Tax Service Office. The results of this study also prove that simultaneously work competence, work loyalty, work discipline, and performance allowances have a positive and significant effect on employee performance at the Bantul Pratama Tax Service Office.